1991
DOI: 10.1073/pnas.88.20.9360
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of glutathione synthesis in the newborn rat: a model for endogenously produced oxidative stress.

Abstract: A model for oxidative stress is described in which glutathione (GSH) synthesis is selectively blocked in newborn rats by administration of L-buthionine-(SR)-sulfoxipuine (BSO). In this model, the normal endogenous physiological formation of reactive oxygen species is largely unopposed, and therefore oxidative tissue damage occurs; because GSH is used for reduction of dehydroascorbate, tissue ascorbate levels decrease. In lung there are decreased numbers of Isieflar bodies and decrease of intraalveolar surfacta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
82
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(87 citation statements)
references
References 57 publications
5
82
0
Order By: Relevance
“…The lethal effects of excessive GSH deficiency in animals such as new born rats and guinea pigs appear to be related to multiorgan failure, involving mitochondrial and other damage in liver, kidney and lung (Martensson et al, 1991). Our results also provide significant evidence that GSH depletors induce intracellular GSH deficiency and enhance CDDP-induced cytotoxicity in bladder cancer cells, whereas GSH depletor alone had no significant cytotoxicity effect at the concentration and exposure time used in this study.…”
Section: Measurement Of Intracellular Ros Generationsupporting
confidence: 52%
See 1 more Smart Citation
“…The lethal effects of excessive GSH deficiency in animals such as new born rats and guinea pigs appear to be related to multiorgan failure, involving mitochondrial and other damage in liver, kidney and lung (Martensson et al, 1991). Our results also provide significant evidence that GSH depletors induce intracellular GSH deficiency and enhance CDDP-induced cytotoxicity in bladder cancer cells, whereas GSH depletor alone had no significant cytotoxicity effect at the concentration and exposure time used in this study.…”
Section: Measurement Of Intracellular Ros Generationsupporting
confidence: 52%
“…It has been demonstrated that CDDP induced nephrotoxicity can be presented by GSH in renal tissues (Anderson et al, 1990). Furthermore, it has been reported that GSH reacts with ROS and plays a role in the reduction of hydrogen peroxide and organic peroxides (Meister, 1983;Martensson, 1991) and that CDDP is inactivated by direct binding to GSH (Meijer et al, 1990). Ishikawa et al (1993) showed that CDDP reacts with intracellular GSH and that the resulting glutathione-platinum complex is actively exported from leukaemia cells via a GS-X pump.…”
Section: Measurement Of Intracellular Ros Generationmentioning
confidence: 99%
“…GSH is a well known antioxidant that directly reacts with free radicals and serves as a cofactor for GSH peroxidase to reduce hydrogen peroxide, resulting in reduction of the oxidative cellular environment (38). Using the fluorescent probe DHR123, we demonstrated that reduced ROI levels indeed occurred in several independently established cell lines containing elevated GSH levels (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…This is analogous to the situation in higher eukaryotes, in which depletion of GSH induced by treatment with L-buthionine(S,R)-sulfoximine leads to oxidative tissue damage along with the breakdown of mitochondria (Martensson et al, 1991). Recently, GSH was also found to be essential in Schizosaccharomyces pombe and a role in the detoxification of endogenously derived metabolites via a GSH-conjugate pump was proposed (Chaudhuri et al, 1997).…”
Section: Introductionmentioning
confidence: 85%